Analyse des euphémismes dans les discours de Gabriel Attal - Rizki Aulia; Elvi Syahrin (Didacticofrancia Journal Didactique du FLE, 2026)
he process of this research aims to describe and analyze the classifications of euphemisms found in three speeches of Gabriel Attal, namely the inaugural speech as Prime Minister (January 9, 2024), the general policy declaration at the National Assembly (January 30, 2024), and the handover speech (September 5, 2024). This research employs a descriptive qualitative method with content analysis based on Samoskaite’s (2011) classification of euphemisms. The research stages include data collection from official transcripts, identification of euphemistic expressions, classification into categories, and analysis of their frequency. The results show 66 euphemisms across six categories, with the political classification being the most dominant at 76% (51 cases), followed by criminal (9%), professional (8%), death (5%), and disease (2%). No sexual euphemisms were identified. These findings indicate that political euphemisms play a crucial role in Gabriel Attal’s discursive strategy to mitigate sensitive issues, maintain a positive public image, and foster persuasive, diplomatic communication.